THE EFFECTIVENESS OF ROSE FLOWER (ROSA CHINENSIS JACQ) ON CANDIDA ALBICANS COLONIES IN JELLY (SABOURAUD DEXTROSE AGAR) MEDIA - Widyana, Erni Dwi; Tarsikah, Tarsikah; Naimah, Naimah (Public Health of Indonesia, 2019)
Background: Approximately 90% of women in Indonesia have the potential to experience fluor albus. Fluor albus is mostly caused by Candida Albicans. Candida Albicans is a fungus that often causes infections on people. Herbal medicine is one alternative that can be used as a raw material for anti-fungial medication of Candida Albicans.Objective: The purpose of this study was to determine effectiveness of rose flower (Rosa Chinensis Jacq) on Candida Albicans colonies.Methods: This research was an experimental study with posttest only control group design, using four repetitions with a concentration of 7.5%, 10%, 12.5%, 15% and 17.5%. The hypothesis test used was One-way ANOVA (Analysis of Variance) with a significance level of 0.05.Results: The result shows that 7.5% concentration, the growth of the colonies was 148.75 CFU/ml; at 10% concentration, the growth of the colonies was 123 CFU/ml; at 12.5%, the growth of the colonies was 86 CFU/ml, at 15%, the growth of the colony was 29 CFU/ml; at 17.5 %, the colony growth was 0, so it can be concluded the higher concentration of rose extract, the lower number of Candida Albicans colonies.Conclusion: Rose extract (Rosa Chinensis Jacq) is effective in inhibiting the growth of the Candida Albicans fungus with minimum killing levels of 17.5%. Further studies on toxicity test on rose extracts on Candida Albicans are necessary.